Cell-Target-Specific Anti-Inflammatory Effect of Empagliflozin: In Vitro Evidence in Human Cardiomyocytes - Giannattasio, Silvia; Citarella, Anna; Trocchianesi, Sofia; Filardi, Tiziana; Morano, Susanna; Lenzi, Andrea; Ferretti, Elisabetta; Crescioli, Clara (Frontiers in Molecular Biosciences, 2022)
The antidiabetic sodium-glucose cotransporter type 2 inhibitor (SGLT2i) Empagliflozin efficiently reduces heart failure (HF) hospitalization and cardiovascular death in type 2 diabetes (T2D). Empagliflozin-cardioprotection likely includes anti-inflammatory effects, regardless glucose lowering, but the underlying mechanisms remain unclear. Inflammation is a primary event in diabetic cardiomyopathy (DCM) and HF development. The interferon (IFN)γ-induced 10 kDa protein (IP-10/CXCL10), a T helper 1 (Th1) type chemokine, promotes cardiac inflammation, fibrosis and diseases, including DCM, ideally representing a therapeutic target. This preliminary study aims to explore whether Empagliflozin directly affects Th1-challenged human cardiomyocytes, in terms of CXCL10 targeting. To this purpose, Empagliflozin dose-response curves were performed in cultured human cardiomyocytes maintained within a Th1-dominant inflammatory microenvironment (IFNγ/TNFα), and CXCL10 release with intra-cellular IFNγ-dependent signaling path (Stat1) were investigated. To verify possible drug cell-target specificity, the same assays were run in human skeletal muscle cells. Empagliflozin dose-dependently inhibited CXCL10 secretion (IC50=76,14x10-9 M) in association with Stat-1 path impairment only in Th1-induced human cardiomyocytes, suggesting drug-selective cell type-targeting. As CXCL10 plays multifaceted functions in cardiac remodeling towards HF and currently there is no effective method to prevent it, these preliminary data might be hypothesis generating to open new scenarios in the translational approach to SGLT2i-dependent cardioprotection.